Analisis Kesalahan Matematika Siswa Dalam Menyelesaikan Soal Operasi Penjumlahan Pecahan Bentuk Aljabar - Herna Herna (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2017)
This qualitative research was conducted at Junior High School students and aimed to examine students' mathematical errors in subject matter of addition operation of algebraic shapes. The subjects of this research were class VIII SMP Negeri 1 Tinambung, Polman, Sulawesi Barat which made the most error variations. This research found that students make mathematical errors in completing the sum of Algebra operating problems. These errors include the errors in fractional addition operands, algebraic forms, and algebraic operations form. Furthermore, it is found that the mistakes made by the students in solving the problem were related to met-before students.